'The Anglo-Irish Agreement put us on side with the Americans': Margaret Thatcher, Anglo-American relations and the path to the Anglo-Irish Agreement, 1979-1985. Issue 3 (2nd July 2020) - Kelly, Stephen
ABSTRACT: This article offers a critical re-evaluation of British prime minister, Margaret Thatcher's relationship with U.S president, Jimmy Carter (1977–1981) and his successor, Ronald Reagan (1981–1989), in the context of the Northern Ireland conflict from 1979 to 1985. Specifically, it examines the impact that the 'Irish Question' had on the changing nature of Anglo-American relations from Thatcher's entry to No. 10 Downing Street in May 1979 to the signing of the Anglo-Irish Agreement (AIA) in November 1985.